A mutation creating an out‐of‐frame alternative translation initiation site in the GRHPR 5′UTR causing primary hyperoxaluria type II. (26th December 2014) - Fu, Y.; Rope, R.; Fargue, S.; Cohen, H.T.; Holmes, R.P.; Cohen, D.M.
<x xml:space="preserve">Abstract</x> Primary hyperoxaluria type II is a recessive genetic disorder caused by mutations in the GRHPR gene. Although several dozen mutations have been described, all affect coding or transcript splicing. A man suspected of having primary hyperoxaluria type II was heterozygous for a novel single‐nucleotide deletion (c.694delC) in GRHPR affecting Gln232, which introduced a pre‐mature termination (p.Gln232Argfs*3). Two 5′untranslated region (UTR) variants of unknown significance were also noted. We show that these two variants occur in cis, on the opposite allele, and introduce – immediately upstream of the canonical translation initiation site – a novel out‐of‐frame translational start site. In vitro studies using the GRHPR 5′UTR fused to a luciferase reporter show that the variant start site pre‐empted initiation at the canonical translational start site, and this was corroborated within the broader context of 1.3 kb of the GRHPR proximal promoter. This latter mechanism may be underappreciated in general; reports of clinically significant functional variation of this type are extremely rare.